2012
DOI: 10.1063/1.4729867
|View full text |Cite
|
Sign up to set email alerts
|

An energy-tunable positronium beam produced using the photodetachment of the positronium negative ion

Abstract: We report here the production of an energy-tunable monoenergetic positronium beam using photodetachment of the positronium negative ion, a bound state of one positron and two electrons. The ions were produced efficiently by bombarding a Na-coated tungsten surface with a pulsed slow positron beam and accelerated using a static electric field. On irradiating the ions with a high intensity pulsed laser light, a positronium beam with a hitherto unrealized energy range of up to 1.9 keV has been produced in an ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…This was first suggested by Mills [509], but has only recently been demonstrated following the experimental advances made by the Tokyo group (see Fig. 36) [120,559]. Energy tunable Ps beams can be made by passing a positron beam through a gas cell [85,231,560,561], or by glancing angle positron scattering [562].…”
Section: Ps − Spectroscopymentioning
confidence: 99%
“…This was first suggested by Mills [509], but has only recently been demonstrated following the experimental advances made by the Tokyo group (see Fig. 36) [120,559]. Energy tunable Ps beams can be made by passing a positron beam through a gas cell [85,231,560,561], or by glancing angle positron scattering [562].…”
Section: Ps − Spectroscopymentioning
confidence: 99%
“…Some of the γ-rays from positron annihilations in the target were detected by the MCP and gave information on the time of the Ps formation. The time interval of the detections of this γ-ray and the Ps clearly showed that the Ps flew with the energy expected from the electrostatic acceleration of the Ps − ions [5]. Production of an energy-tunable Ps beam from 300 eV to 1.9 keV in an ultra-high-vacuum environment was achieved.…”
Section: Ps Negative Ion Experiments Stationmentioning
confidence: 90%
“…Immediately after that, the photodetachment was accomplished by irradiation of 25 Hz pulsed (width 12 ns) Qswitched Nd:YAG laser. Since the slow positron beam is provided in 50 Hz, the data with and After developing the above technique, we built a new beam-line branch, SPF-A3, and an energy-tunable Ps beam was successfully produced in ultra-high-vacuum environment and detected [5]. The energy of the Ps, which is a neutral atom and hence cannot be accelerated by a static electric field directly, tuned accelerating the Ps − ions before the photodetachment.…”
Section: Ps Negative Ion Experiments Stationmentioning
confidence: 99%
“…Ionizing potential of this negative Ps ion is 0.33 eV. In the setup described by Michishio et al [20] the monoenergetic beam of positrons bombards the target of tungsten foil covered by a monolayer of Na. The Ps _ ions emitted from this surface (efficiency about 1.5%) are accelerated by a static electric field.…”
Section: Namentioning
confidence: 99%